Use of recycled sand as a corrective material for soil acidity in soybean crops - Vazquez, Gisele Herbst; Sanches, Andréa Cristiane; Santos, Mateus Leonardo Welika dos (Electronic Journal "Fórum Ambiental da Alta Paulista", 2022)
Acidity is one of the main factors capable of reducing the productive potential of Brazilian soils, as it promotes the release of toxic elements for plants and reduces the availability of nutrients. Recycled civil construction and demolition waste (R-CCW class A) is a major environmental problem in Brazilian cities, especially in terms of its illegitimate disposal, causing floods, clogging of galleries and silting of channels, in addition to the proliferation of vectors and pollution. The objective of this study was to evaluate the potential of recycled sand (R-CCW) as a corrective of soil acidity, through soybean cultivation, in an experiment installed in PVA1 yellow-reddish with sandy/medium texture, acid and of low fertility with doses of 10, 20 and 40% of R-CCW, by mass, in Fernandópolis/SP. Variables related to soil fertility and to plants that were subjected to analysis of variance by F and comparison of averages by the Skott-Knott test at 5% probability were evaluated. The results obtained allowed us to conclude that recycled sand from civil construction R-CCW class A has favorable effects in terms of its ability to neutralize H+ ions in the soil solution and those adsorbed to negative soil charges, important effects as an acidity corrective, in addition to providing increases in the contents of Ca, Mg, SB, CEC and V%, greater development of soybean plants, which indicates that this use is an environmentally correct alternative for the disposal of these residues.